Yoga Program for Type 2 Diabetes Prevention (YOGA-DP) Among High-Risk People: Qualitative Study to Explore Reasons for Non-participation in a Feasibility Randomized Controlled Trial in India - Pallavi Mishra; Sheila Margaret Greenfield; Tess Harris; Mark Hamer; Sarah Anne Lewis; Kavita Singh; Rukamani Nair; Somnath Mukherjee; Nandi Krishnamurthy Manjunath; David Ross Harper; Nikhil Tandon; Sanjay Kinra; et al. (Frontiers Media S.A., 2021)
Background: Yoga-based interventions can be effective in preventing type 2 diabetes mellitus (T2DM). We developed a Yoga program for T2DM prevention (YOGA-DP) among high-risk people and conducted a feasibility randomized controlled trial (RCT) in India. The objective of this study was to identify and explore why potential participants declined to participate in the feasibility RCT.Methods: An exploratory qualitative study, using semi-structured interviews, was conducted at a Yoga center in New Delhi, India. Fourteen people (10 women and four men) who declined to participate in the feasibility RCT were interviewed, and 13 of them completed the non-participant questionnaire, which captured their socio-demographics, diets, physical activities, and reasons for declining.Results: Three types of barriers were identified and explored which prevented participation in the feasibility RCT: (1) personal barriers, such as lack of time, perceived sufficiency of knowledge, preferences about self-management of health, and trust in other traditional and alternative therapies; (2) contextual barriers, such as social influences and lack of awareness about preventive care; and (3) study-related barriers, such as lack of study information, poor accessibility to the Yoga site, and lack of trust in the study methods and intervention.Conclusions: We identified and explored personal, contextual, and study-related barriers to participation in a feasibility RCT in India. The findings will help to address recruitment challenges in future Yoga and other RCTs.Clinical Trial Registration:www.ClinicalTrials.gov, identifier: CTRI/2019/05/018893.